Electromagnetically induced absorption resonances in Hanle-configuration prepared in a paraffin coated 87Rb cell. (April 2020) - Taskova, E; Alipieva, E; Andreeva, C; Brazhnikov, D
Abstract: We present an experimental investigation of electromagnetically-induced absorption (EIA) at the D1 line of 87 Rb contained in an anti-relaxation coated vacuum optical cell. The configuration includes a pump and a probe beam propagating in opposite directions and having mutually orthogonal linear polarizations; the probe beam absorption is registered depending on the value of a magnetic field scanned around zero and applied collinearly to the laser beams. The advantages of this scheme have been recently evidenced in vapor cells filled with a buffer gas. In the present work we studied the width and the contrast of the EIA resonances obtained in a coated cell for different values of the pump power. The results are compared with those obtained in a buffer gas cell for the same transition of 87 Rb. The theoretical calculations are in good agreement with the experiment.